2015
DOI: 10.1115/1.4029796
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Combined Effects of Rotational Inertia and Viscosity–Pressure Dependency on the Squeeze Film Characteristics of Parallel Annular Plates Lubricated by Couple Stress Fluid

Abstract: This study presents combined effects of couple stress fluids and rotational inertia together with considering lubricant viscosity variation with pressure in squeeze film characteristics of parallel annular plates. Squeeze film characteristics are obtained by combined solution of modified Reynolds equation and Stoke's microcontinuum for couple stress fluids with consideration of viscosity variation with pressure. Various cases of couple stress, inertial and non-inertial characteristics with iso-viscous and piez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…For lubricated parallel annular discs, combined with squeeze film and shear motions, Daliri et al [7] showed that contact load-carrying capacity increases by the presence of magnetohydrodynamic couple stress fluids. For the same geometry of parallel annular plates, however, increased rotational inertia can diminish the squeeze film characteristics [8]. Parallel disc lubrication film geometry, with rough surfaces where the lubricant is piezoviscous couple stress, is also studied by Daliri and Jalali-Vahid [9].…”
Section: Introductionmentioning
confidence: 99%
“…For lubricated parallel annular discs, combined with squeeze film and shear motions, Daliri et al [7] showed that contact load-carrying capacity increases by the presence of magnetohydrodynamic couple stress fluids. For the same geometry of parallel annular plates, however, increased rotational inertia can diminish the squeeze film characteristics [8]. Parallel disc lubrication film geometry, with rough surfaces where the lubricant is piezoviscous couple stress, is also studied by Daliri and Jalali-Vahid [9].…”
Section: Introductionmentioning
confidence: 99%
“…Daliri, Metet et al [1] analyzed the viscosity variation with pressure to obtain squeeze film characteristics by modified Reynolds equation and Stoke's microcontinuum. Jaw-Ren Lin et al [2] analyzed the effects of viscosity-pressure dependency and studied the impacts of squeezed films between parallel circular plates of non-Newtonian coupled stress fluid lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…To relieve rigid impact and promote torque capacity during the extrication of the cutter-head, the hydro-viscous clutch (HVC) has recently been applied to the driving system of the TBM cutter-head by many researchers, and the inside structure and working principle of the HVC have been introduced [1][2][3][4]. Liao et al [5][6][7][8][9] designed a new kind of cutter-head driving system which includes a flywheel and HVC in each cutter-head driving chain, and the popular variable-frequency method is still used.…”
Section: Introductionmentioning
confidence: 99%